STUDENTS' MOTIVATION TO WEAR THE VEIL IN YASNI BUNGO JAMBI ISLAMIC INSTITUTE - Januri Januri; M. Syukri Ismail (Islamuna: Jurnal Studi Islam, 2021)
ABSTRACT The veil is a Muslim woman's face covering, only her eyes are visible. Wearing the veil requires faith, mental and strong motivation. This study aims to examine the motivations of IAI student Yasni Bungo to wear the veil. This study uses a qualitative descriptive analytical approach. Data was collected by using observation, interview and documentation techniques. Determination of research subjects using purposive sampling technique, by interviewing female students who only wear the veil. The data analysis technique was carried out by listening to the interviews of female students wearing veils, recording their interviews, grouping the results of the interviews, analyzing the results of the interviews and conclusions. The results of the study indicate that the motivation for using the veil by IAI student Yasni Bungo is motivated by three factors, first, theological factors (students wear the veil because of religious orders, worship, sunnah of the prophet); second is psychological factors (students wear the veil because they are driven by a soul that feels comfortable when wearing the veil), and third, the intrinsic factor (students wear the veil to protect themselves, keep morals, to be better, more obedient). And there are no external factors (veiled because parents, teachers, ustadz ordered them, the rules of the Islamic Boarding Schools, or were motivated by the doctrine of forbidden sects). The more dominant factor is the theological factor. ABSTRAK Cadar merupakan penutup wajah wanita muslimah, yang nampak hanya kedua matanya. Memakai cadar dibutuhkan keyakinan, mental dan motivasi yang kuat. Penelitian ini bertujuan untuk mengkaji apa saja motivasi mahasiswi IAI Yasni Bungo memakai cadar. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif analitis. Pengumpulan data dilakukan dengan teknik observasi, wawancara dan dokumentasi. Penentuan subjek penelitian menggunakan teknik purposive sampling, dengan mewancarai mahasiswi yang memakai cadar saja. Teknik analisis data dilakukan dengan cara menyimak wawancara mahasiswi yang memakai cadar, mencatat wawancaranya, mengelompokkan hasil wawancaranya, menganalisis hasil wawancaranya dan membuat kesimpulan. Adapun hasil penelitian menunjukkan bahwa motivasi penggunaan cadar oleh mahasiswi IAI Yasni Bungo dilatarbelakangi oleh tiga faktor, yaitu pertama, faktor teologis (mahasiswi memakai cadar karena perintah agama, ibadah, sunnah nabi); kedua faktor psikologis (mahasiswi memakai cadar karena terdorong oleh jiwa yang merasa tenang-nyaman ketika memakai cadar), dan ketiga, faktor intrinsik (mahasiswi memakai cadar untuk menjaga diri, jaga akhlak, agar lebih baik, lebih taat). Dan tidak ada faktor eksternal (bercadar karena disuruh orang tua, guru, ustadz, aturan pesantren, atau terdorong oleh doktrin aliran terlarang). Adapun faktor yang lebih dominan adalah faktor teologis.